Lexical borrowing in the light of digital resources: 'Nyet' as a case study - Podhajecka, Mirosława (Adam Mickiewicz University, 2021)
The mere appearance of a foreign word does not necessarily mark the birth of a loanword, which requires documented usage by the speech community. Relatively little research has been dedicated so far to the “prenatal” stage that would investigate the tentative infiltration of foreign-derived words. Nyet, a borrowing from Russian, is taken as a case in point. Although its first recorded instance in the Oxford English Dictionary (OED3) is dated to 1928, it had been increasingly recognized in English for several decades. This article focuses on textual attestations for nyet discovered in a range of digital resources, including British and American newspaper archives, and discusses their usefulness as potential antedatings for OED3’s entry.
Keywords: OED3; nyet; loanword; Russian; citation; antedating; British English; American English; digital resources